The position of the DPRD as an equal partner to the Regional Head according to Law no. 23 of 2014 - Mochammad Rayhan Widiyasmoro; Labib Mutaqqin (Proceeding International Conference Restructuring and Transforming Law, 2023)
Indonesia in running its government uses a decentralized or centralized system. The main objective is for each region to have the ability to control and utilize regional autonomy as much as possible and not be disturbed by outside interests. In the process, the principle of decentralization undergoes changes above its laws, both to its object and subject. Contained in Law Number 23 of 2014 which is an amendment of Law Number 32 of 2004 which puts the DPRD as a partner for regional heads which was originally a legislative institution for regional government. And finally, the duties and authorities of a member of the DPRD also underwent changes that were not too significant. This research will focus on Law Number 23 of 2014 both historically and sociologically regarding the changes in it. This research uses juridical‐normative research methods by focusing on laws, doctrines, and jurisprudence.